Preparation of C4-silica Gels from Waste Glass and Tributylamine - Nelly Wahyuni; Rudiyansyah Rudiyansyah; Mellisa N. Safitri (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2019)
Waste glass materials coming from municipal and industrial processes have become a serious problem for the environment in the near future. Silica gels have been long attracting attention since it is widely used for many applications. It had also been studied by several fields because of its surface properties. In this study, semi-polar silica gels have been synthesized. C4-silica gels have been prepared by reaction between tributylamine (TBA) and silica gels produced from waste glass. The waste glass was powdered, soaked in NaOH, then heated at 400 oC to obtain sodium silicate. Silica gels were produced by neutralized the sodium silicate using HCl, dissolved in H2O, and dried in an oven at 80 oC. Silica gels were solubilized in TBA, stirred, and dried in the oven to obtain C4-silica gels. Silica gels were characterized by X-ray Diffraction (XRD), while Infra Red (IR) and Scanning Electron Microscopy (SEM) analyses were conducted to obtained C4-silica gels. XRD analysis of silica gels showed that the highest peak intensity was observed at 2θ = 22.655°. The band at 1381.03 cm-1 in the IR spectrum was attributed to the nitro-oxygen bond (N-O). SEM images showed that the surface of C4-silica gels was smoother and more flat than the previous silica gels.